(untitled) (Texas Journal of Philology, Culture and History, 2021)
One of the most contentious questions in international politics is the question of the definition of terrorism. Perhaps one of the better-known aphorisms is that “one man’s terrorist is another man’s liberation fighter.”1 It is not accidental that this aphorism emerged within the context of the liberation struggles in Southern Africa in which the settlers/colonial oppressors described freedom fighters as terrorists and created the impression that the liberation armies were rebels without a just cause. A definition seems controversial for reasons other than conceptual issues and problems